2022
DOI: 10.3390/brainsci13010067
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Language and Thought in Human Reasoning

Abstract: What is the relationship between language and complex thought? In the context of deductive reasoning there are two main views. Under the first, which we label here the language-centric view, language is central to the syntax-like combinatorial operations of complex reasoning. Under the second, which we label here the language-independent view, these operations are dissociable from the mechanisms of natural language. We applied continuous theta burst stimulation (cTBS), a form of noninvasive neuromodulation, to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 119 publications
(220 reference statements)
0
1
0
Order By: Relevance
“…However, significant stimulation effects appeared in different behavioral indices of different syntactic tasks. For instance, no accuracy differences but differences in eye-tracking indices could be found during a syntactic ambiguity resolution task after cTBS ( Acheson & Hagoort, 2013 ), whereas accuracy was significantly decreased for a grammaticality judgment task after cTBS to LpIFG ( Coetzee et al, 2023 ). In our study, neither Δ d ′ nor Δ RT showed statistical differences in the conditions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, significant stimulation effects appeared in different behavioral indices of different syntactic tasks. For instance, no accuracy differences but differences in eye-tracking indices could be found during a syntactic ambiguity resolution task after cTBS ( Acheson & Hagoort, 2013 ), whereas accuracy was significantly decreased for a grammaticality judgment task after cTBS to LpIFG ( Coetzee et al, 2023 ). In our study, neither Δ d ′ nor Δ RT showed statistical differences in the conditions.…”
Section: Discussionmentioning
confidence: 92%
“…As a convenient protocol for stimulating the brain for a relatively short period (∼40 s), cTBS has been utilized in several recent studies to establish the causal link between the neural activity of LpIFG and syntactic processing ( Acheson & Hagoort, 2013 ; Coetzee et al, 2023 ). However, significant stimulation effects appeared in different behavioral indices of different syntactic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Young children’s general intelligence (g factor) plays a significant role in their cognitive skills progress ( Almamari and Traynor 2021 ; Gomes et al 2014 ; Panizzon et al 2014 ). Moreover, language is central in the operations of children’s complex cognitive tasks, especially in deductive reasoning ( Coetzee et al 2023 ). It is also possible that the country of residence has a stronger influence on educational systems and teaching methods, which in turn affect deductive reasoning skills.…”
Section: Introductionmentioning
confidence: 99%